Development of E-Modules Based on Socio-Scientific Issues to Improve Students' Science Literacy Skills on Temperature and Heat Materials - Silvia, Risma Mega; Hertanti, Erina; Suryadi, Ahmad (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2024)
E-modules on temperature and heat material have been developed in several studies, but there are still problems. The problem is that it does not facilitate students to practice science literacy skills so it is still relatively low. This research aims to minimize these problems by developing e-modules based on socio-scientific issues to improve students' science literacy skills in temperature and heat materials. The method used is Research and Development with a 4D development design consisting of 4 main stages, namely: Define, Design, Develop and Disseminate. This research is limited to the Develop stage. The e-module testing is feasible through validity, practicality, and effectiveness tests. The test results show that the e-module is suitable for use because it is categorized as valid, practical, and effective. E-modules are categorized as valid with the results of the assessment of excellent material experts, good media experts, and excellent linguists. E-modules are categorized as practical with the results of response questionnaires in small groups, field groups, and teachers showing positive evaluations. E-modules are categorized as moderate or effective in improving students' science literacy skills.